The judicialization of antidepressant medicines in Brazil: Scope review (Research, Society and Development, 2024)
Introduction: The judicialization of medicines has generated debates about the efficacy, effectiveness and efficiency of the Brazilian health system and the need for reforms to improve access to treatments. Objective: To map the process of judicialization of antidepressant medications in Brazil and its influence on the management capacity of pharmaceutical assistance in mental health care. Method: Scope review. Results: 35 scientific publications were retrieved. 9 were excluded due to duplicate records. 8 were removed because they did not meet the inclusion criteria. 2 were restricted access. 1 presented incompatible methodology. 15 were selected. Of the 15 works selected, 8 were articles, 4 master's theses, 2 doctoral theses and 1 undergraduate course completion work. There are, therefore, 6 publications from 2022, 5 from 2019, 3 from 2021, 2 from 2023 and 1 from 2020. Conclusion: It is inferred that judicial decisions in favor of the supply of medicines compromise the process of governance, planning, and management of the Unified Health System (SUS), damaging the budget/financing, increasing expenses, disorganizing the flow, and compromising its sustainability.